Critical Chemical-Quality Assessment for the Oxidative Stability of Bulk Palm Oil in Indonesia - Drajat Martianto; Nuri Andarwulan; Donald Siahaan; Desty Gitapratiwi; Ria Noviar Triana; Purwiyatno Hariyadi (International Journal of Oil Palm, 2018)
The main objective of this study was to assess the quality of bulk palm oil from the point of production (and its distributors) using the critical factors of vitamin A stability and carotenoids (expressed as beta-carotene) in Indonesia. The specific objectives were to analyze the peroxide value (PV), acid value of free fatty acid (FFA) and carotenoids (expressed as beta-carotene) content of unfortified bulk palm oil in Indonesia. The study showed that the quality of initial bulk palm cooking oil, both at the level of manufacturers and distributors, was inconsistent; however, it was still in compliance with the Indonesian standard for cooking oil (SNI 7709-2012). The PV and FFA range of bulk palm cooking oil analyzed was 0-8.94 meq O2 kg-1 and 0.06-0.23% respectively, and the range of carotenoids content (expressed as beta-carotene) was quite low, only 1.2-3.05 ppm, respectively. The results of this study could be used as the basis of vitamin A fortification in palm oil, since the stability of the fortificant in the oil would be affected by the initial chemical quality, especially its FFA and PV content